Promoting Intercultural Communication in CCU Classroom of EFL students by Using VCT - Hidayati, Fithriyah Nurul; Fatmawati, Nor Laili; Muntaha, Muntaha (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Background Adapting to diverse communication practices prevents conflicts and promotes smoother interactions. It necessitates innovations like Virtual Culture Tour (VCT) in CCU learning. VCT provides real-world and interactive cultural learning. This research explores VCT's implementation in EFL CCU classrooms to enhance intercultural communication and surveys student responses. Methodology The research uses a mixed-method approach, combining qualitative data from CCU classroom observations and interviews at UIN Raden Mas Said Surakarta and Maritim Class of Global English Course, and quantitative data from questionnaires surveying the students' responses. Findings The use of VCT in CCU classrooms has effectively promoted intercultural communication for EFL students. In formal classes at PBI UIN Raden Mas Said Surakarta, VCT followed a structured process, including guided tours and virtual interactions with native speakers. Non-formal classes offered more flexibility, allowing students to explore at their own pace and engage in follow-up communication activities. Students responded positively, with 95.82% strongly agreeing on VCT's effectiveness. These findings highlight VCT's success in enhancing intercultural communication. Conclusion The use of VCT in CCU classrooms has promoted EFL students’ intercultural communication in both formal and non-formal learning contexts because of its flexible steps of implementation. It encouraged students to respond positively to the use of VCT in CCU classrooms. Originality This study highlights the novelty of using VCT as a digital tool to overcome space, time, and financial barriers in promoting intercultural communication in CCU classrooms. It also explores VCT's implementation in formal and non-formal learning settings and surveys students' responses.